Threat of political vigilantism to political security in Africa: a case of Ghana - Emmanuel Papa Bentil; Isaac Nunoo; Maxwell Oduro Appiah (Cogent Social Sciences)
Ghana is gradually building a political culture that seems to support political vigilantism. This is because the activities of vigilante groups have assumed a cyclonic nature. This study, therefore, seeks to assess the threat of political vigilantism to political security in Ghana and the roles of state and non-state actors in all of this. It explores the sources and the motivations for acts of political vigilantism and addresses the threat of political vigilantism to political security in Ghana. It also analyses the implications of political vigilantism on security issues and Ghana’s global image. Lastly, it discusses the roles of state and non-state actors in mitigating the threat of political vigilantism to political security. Relying on interviews and documents, the study demonstrates that unemployment and the vulnerability of the youth, mutual suspicion among the political actors, and low confidence in state institutions motivate political vigilantism in Ghana. Political vigilantism is also found to have strong association with clientelism in Ghana. It is recommended that both state and non-state actors adopt a broad-based approach to confront the problem frontally.